Hippo-YAP signaling controls lineage differentiation of mouse embryonic stem cells through modulating the formation of super-enhancers. Issue 13 (8th June 2020) - Sun, Xiang; Ren, Zhijun; Cun, Yixian; Zhao, Cai; Huang, Xianglin; Zhou, Jiajian; Hu, Rong; Su, Xiaoxi; Ji, Lu; Li, Peng; Mak, King Lun Kingston; Gao, Feng; et al.
Abstract: Hippo-YAP signaling pathway functions in early lineage differentiation of pluripotent stem cells, but the detailed mechanisms remain elusive. We found that knockout (KO) of Mst1 and Mst2, two key components of the Hippo signaling in mouse embryonic stem cells (ESCs), resulted in a disruption of differentiation into mesendoderm lineage. To further uncover the underlying regulatory mechanisms, we performed a series of ChIP-seq experiments with antibodies against YAP, ESC master transcription factors and some characterized histone modification markers as well as RNA-seq assays using wild type and Mst KO samples at ES and day 4 embryoid body stage respectively. We demonstrate that YAP is preferentially co-localized with super-enhancer (SE) markers such as Nanog, Sox2, Oct4 and H3K27ac in ESCs. The hyper-activation of nuclear YAP in Mst KO ESCs facilitates the binding of Nanog, Sox2 and Oct4 as well as H3K27ac modification at the loci where YAP binds. Moreover, Mst depletion results in novel SE formation and enhanced liquid-liquid phase-separated Med1 condensates on lineage associated genes, leading to the upregulation of these genes and the distortion of ESC differentiation. Our study reveals a novel mechanism on how Hippo-YAP signaling pathway dictates ESC lineage differentiation.